2020
DOI: 10.1002/batt.202000244
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Chloroaluminate Melts for Aluminum Graphite Dual‐Ion Battery Application

Abstract: Herein, we report a comparison of aluminum graphite dual‐ion cells (AGDICs) electrochemical characteristics employing the conventional 1‐ethyl‐3‐methylimidazolium chloride:aluminum trichloride (EMIMCl : AlCl3) electrolyte and two popular deep eutectic solvents (DESs), namely urea : AlCl3 and acetamide:AlCl3. The three electrolytes′ characteristics have been evaluated in terms of Al‐stripping deposition capability and cycling behavior in AGDICs. The results evidence the EMIMCl : AlCl3′s Al‐stripping deposition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The detailed information of these electrolytes is provided in Table S1 (Supporting Information). [14,16,17,[26][27][28] It can be seen that although the displacement of organic salts in chloroaluminate ILs can improve the high-voltage stability, all electrolytes with no additive show oxidation onset potential below 2.6 V versus Al 3+ /Al. With the additive of LiBOB, an IL electrolyte of AlCl 3 /[EMIm]Cl can deliver a good high-voltage stability at 100 °C.…”
Section: Resultsmentioning
confidence: 99%
“…The detailed information of these electrolytes is provided in Table S1 (Supporting Information). [14,16,17,[26][27][28] It can be seen that although the displacement of organic salts in chloroaluminate ILs can improve the high-voltage stability, all electrolytes with no additive show oxidation onset potential below 2.6 V versus Al 3+ /Al. With the additive of LiBOB, an IL electrolyte of AlCl 3 /[EMIm]Cl can deliver a good high-voltage stability at 100 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, Azimi et al reported conductivities decreasing from 22.6 to 14.7 mS cm –1 for LA:LB compositions between 1:1 and 2:1 with AlCl 3 :EMIM-Cl liquids . Other reports have found conductivities of 16.1, 15.5, and 9.2 mS cm –1 for AlCl 3 :EMIM-Cl liquids with a 1.5:1 mole ratio. On the other hand, for urea-based liquids, the conductivities are an order of magnitude lower than that of EMIM-Cl based liquids.…”
Section: Introductionmentioning
confidence: 93%
“…The state-of-the-art electrolytes for room-temperature rechargeable nonaqueous aluminum metal batteries are ionic liquid electrolytes (ILEs) consisting of 1ethyl-3-methylimidazolium chloride (EmimCl) and aluminum chloride (AlCl 3 ). [22] The viscosity of [EmimCl] 1 [AlCl 3 ] 1.5 is reported to be 19.4 mPa s at 20 °C, [23] while the electrolyte viscosity for commercial LIBs is usually lower than 10 mPa s. [24] The high viscosity hinders the penetration of electrolytes into thick electrodes, leading to a low utilization of sulfur encapsulated in porous host materials. [25] It is expected that this negative effect would become more pronounced at sub-zero temperatures due to the further decreased electrolyte fluidity.…”
Section: Introductionmentioning
confidence: 99%